REPRESENTASI SOSIAL DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER (TINJAUAN SOSIOLOGI SASTRA) - Tiopiolina Tiopiolina (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This descriptive study purpose to describe (1) the social reality depicted in Pramoedya Ananta Toer's novel Bumi Manusia, and (2) its implications for literature learning in high school. This research is a type of qualitative descriptive research.. The object of this research is the social reality depicted in the novel Bumi Manusia by Pramoedya Ananta Toer and its implications for learning literature in high school. The data collection method used in this research is the documentation method, to find out the manifestation of the social reality of the people who are told in the novel Bumi Manusia by Pramoedya Ananta Toer. The data that has been collected is processed inductively through data reduction, data presentation, and drawing conclusions. The results of this study are as follows (1) studied various social realities that are told in the novel Bumi Manusia including: descent and family background which greatly affects social status and position in people's lives, both to access education and establish social relations (2) implications or the contribution of this research to the process of learning literature in high school, especially in the twelfth grade.